COVID 19 - Dengue Co-Infection: Socio-Demographic, Clinical and Laboratory Characterestics in a Tertiary Hospital In Bangladesh - Afroze, Samira Rahat; Islam, Md Jubaidul; Khalil, Ibrahim; Banik, Amit; Nesa, Azimun; Afroz, Farhana; Haque, Hasna Fahmima; Yasmin, Sabrina; Uddin Ahmed, Md Asraf; Ahmed, Jamal Uddin; Ahmed, AKM Shaheen; Rahman, Md Raziur; et al. (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Background: Since starting of the SARS-COV 2 pandemic till date, in dengue endemic countries co-infection of COVID -19 and Dengue co-infection remains a healthcare concern and cases have been reported from some Asian countries. Bangladesh being a high endemic region for dengue infection bears risk of significant healthcare burden of such co-infection cases. During the surge of dengue cases during monsoon season in 2021, the possibility of COVID19 - Dengue co-infection cases also increased. Method: This study was carried out in the Department of Internal Medicine and Pulmonology, Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM) General Hospital, Dhaka, Bangladesh from June 2021 to December 2021. Dengue and COVID 19 cases were confirmed as per Bangladesh National guidelines. Result: Total 12 cases including 8 males were diagnosed as dengue –COVID 19 co-infection during the study period. Mean age was 47.0 years. Majority of cases (10) were residing in Dhaka. Among risk factors, 5 cases were known diabetic and 4 cases were hypertensive while 1 case was congenital adrenal hyperplasia. Common presentations were fever (100%), headache (75%), bodyache (66.7%), dry cough (41.7%), nausea, vomiting, abdominal pain, and retro orbital pain were 25% while rash and shortness of breath occurred in 16.7%. Mean duration of fever was 5.8 days and mean recorded highest temperature was 102.5°F. Dengue manifestation was predominant in 8 cases (66.7%). Laboratory investigations revealed following mean values: baseline haematocrit (HCT) 39.9%, initial total white cell count 4.64x109/L, absolute neutrophil-lymphocyte ratio 2.4, lowest platelet count 100.4x109/L, C-Reactive Protein 143.8mg/L, serum ferritin 888.1 ng/ml, D dimer 2.0 µg/ml, LDH 668.1 U/L, serum Aspartate aminotransferase 88.1 U/ L, Alanine aminotransferase 73 U/L. Radiological findings were present in 7(58.3%) cases, among which pneumonitis was predominant (4 cases,57.1%). All cases were managed and followed up as per national guidelines till discharge and no one required critical care. Conclusion: Observation revealed that COVID -19 and Dengue co-infection may occur and if managed adequately fatal outcome can be avoided, even in high risk patients. Therefore, high degree of suspicion of co-infection should be considered in appropriate clinical scenario. J Bangladesh Coll Phys Surg 2023; 41: 44-50